2012
DOI: 10.1007/s00402-012-1600-x
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraobserver reliability of the Crowe and Hartofilakidis classifications in the assessment of developmental dysplasia of the hip in adult patients

Abstract: In conclusion, we have found substantial inter- and intraobserver agreement for Crowe classification and substantial to moderate agreement for Hartofilakidis classification in this study. Both classification systems assess the different aspects of developmental dysplasia of hip in adults. Each system has advantages and disadvantages. We suggest using both of these classifications together to increase the accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
2
3
0
2
Order By: Relevance
“…Our interobserver agreement kappa for the Hartofilakidis classification was 0.76, higher than the radiographic determination of coverage. Other studies reported similar kappa interobserver agreement values within 0.75 and 0.79 (32, 33). The Hartofilakidis classification was more predictive for sufficient intraoperative coverage compared to the stratifications determined by radiographic templating.…”
Section: Discussionsupporting
confidence: 64%
“…Our interobserver agreement kappa for the Hartofilakidis classification was 0.76, higher than the radiographic determination of coverage. Other studies reported similar kappa interobserver agreement values within 0.75 and 0.79 (32, 33). The Hartofilakidis classification was more predictive for sufficient intraoperative coverage compared to the stratifications determined by radiographic templating.…”
Section: Discussionsupporting
confidence: 64%
“…For this reason, we have already described sup-types of low and high dislocation hips 3 for the validated Hartofilakis classification. 48 Furthermore, we agree, with their suggestion that, during preoperative panning, CT-scan evaluation is often needed. 9…”
supporting
confidence: 60%
“…Les classifications de Cr et Ha présentent une reproductibilité intra-observateur inférieure à celle rapportée dans le travail d'Hartofilkadis et al en 2008 [9] mais supérieure à celle rapportée par Kose et al [11] et Gaston et al [14].…”
Section: Discussionunclassified
“…Les classifications de Crowe (objective) et Hartofilakidis (subjective) sont les plus utilisées dans la litté-rature anglo-saxonne. Leur reproductibilité a été validée dans de nombreuses études [9][10][11], mais leur capacités à prédire les difficultés opératoires est remise en cause par de nombreux auteurs [7,12,13]. Parmi les classifications alternatives, on trouve celle proposée et évaluée par Gaston et al en 2009 [14] et celle publiée par Kerboull dès 1987 [2,15,16].…”
Section: Introductionunclassified